ON THE QUESTION OF THE INTERPRETATION OF THE HERO IN UZBEK HISTORICAL NOVELS (Scientific journal of the Fergana State University, 2024)
The article presents artistic interpretations of the image of Boborakhim Mashrab in Uzbek literature since the 80s of the XX century and the poet's life path in novels dedicated to him, as well as the writers' approaches to this issue. At the same time, since the 80s of the last century, attempts to create the image of Mashrab in an Uzbek novel, having won the love of the people, require from the creator not only high skill, but also deep knowledge, the ability to objectively and truthfully reflect the image of this historical character, which found its interpretation in his narratives, legends and stories.